MANAJEMEN STRATEGIS PEMBINAAN PEMBELAJARAN DI SMA - Ahmad Dani; Zakaria Zakaria; Osa Juarsa (Manajer Pendididikan, 2017)
The general objective of this study was to describe the implementation of strategic management in the development of teachers in the field of learning in  Senior High School Purwodadi Musi Rawas Regency. The method used is descriptive qualitative method. The research subjects principal, vice principal areas of the curriculum, teachers, and supervisors. Data collection methods are interviews, observation, and documentation. The results of the research, the principal implementing strategic management in coaching teachers in the field of teaching with the intention that the problems of learning that teachers face daily in the implementation of PBM in the school does not drag that could result in the ineffectiveness of the learning outcomes achieved, so that students disadvantaged , With the coaching staff through the application of strategic management expected by the principal to have all the advantages that exist in each teacher can develop in a sustainable manner so well that makes the profession and their competencies are also well developed that will result directly affects the quality of the PBM and the quality of learning student at the school.